AeU's fourth convocation - Leong, Irene (the sun, 2014)
AeU held its 4th convocation ceremonY at PWTC, Kuala Lumpur. Around 1200 has received their scrolls. The Convocation was graced by ambassadors and representatives from foreign embassies particularly from the 33 ACD countries. Dr David Richard Namwandi, Minister of Education of the Republic of Namibia said " believes in equality and quality education for all Namibians."